Asuhan Kebidanan Pada Ibu Hamil Dengan Kekurangan Energi Kronis (KEK) Di PMB Husnel Hayati Desa Siabu Tahun 2024 - Andari, Fany Vebri; Harmia, Elvira; Miftahurrahmi, Miftahurrahmi (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Chronic Energy Deficiency (KEK) is a condition where a lack of calories and protein persists for a long time and can cause health problems in women of childbearing age and pregnant women. The aim of the research is to provide midwifery care to pregnant women with chronic energy deficiency (KEK) at (Independent Midwife Practice) PMB Husnel Hayati in Siabu Village on 26 May – 30 July 2024. The results of the case study research given to Mrs. Y, with 7 home visits in 10 weeks, the mother said she was gaining less weight, decreased appetite, body weakness so that the mother felt anxious about her pregnancy. Midwifery care provided consists of carrying out a physical examination using the 10T standard including assessing body weight and Upper Arm Circumference (LILA) according to the observation sheet, followed by providing counseling to the patient regarding healthy pregnancy and the pattern of nutritional intake needed during pregnancy, then providing food t addition (PMT). Based on the pregnancy care provided to Mrs. Y, aged 22 years G1P0A0, it was found that her appetite had returned to normal, the mother no longer felt anxious about her pregnancy and her weight, LILA, TFU had increased. The conclusion is that midwifery care provided from the second visit to the next visit always experiences significant progress, the care for these patients is carried out well. It is hoped that healtht woerkers can improve the quality of treatment and health service for pregnant women with cronic energy deficiency quickly, precisely and comprehensively.